POSSIBILITIES OF USING THE LATEST METHODS OF FIXING AND DOCUMENTATION OF INSPECTION OF A PLACE OF ACTION - Ланцедова, Юлія Олександрівна; Остапенко, Людмила Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the article describes the basics of using the 3 D-laser scanning traffic deed (DTD) method as a method of fixing (simultaneously securing sources and documenting their review and collection process), especially in the case of many survey sites. Methods: general scientific methods and logical methods of analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. were used in the work. Results: a systematic outline of the main possibilities for using the method of domestic investigative and expert practice of the discussion is proposed. Discussion: the basic information about the possibilities of using the laser 3 D-scan of the situation of the DTD location in the domestic investigative and expert practice is clarified. Attention is drawn to the fact that the use of a 3 D-laser scanner in practical investigative and expert activities has a number of positive factors. Firstly, it is a very high accuracy of documenting information in graphical form, which makes it possible to reproduce a realistic picture, as well as large-scale modelling of the criminal offense. Secondly - high speed data processing. For example, for a detailed description of a standard one-room apartment in the usual way, it takes 1.5-3 hours or more, while a 3 D-scanner will create a realistic model in a few minutes. Thirdly, the 3 D-scanner has the ability to perform additional functions, for example, creating animations, plans, projections, sections of objects in 2 D format, and more, which allows a thorough analysis of forensic information. Fourth, the procedure for using 3 D-scan technology is simple for specialists to acquire the necessary skills.At the same time, the use of 3 D-laser scanning is associated with a rather high price of software, the mandatory presence of special knowledge and the lack of qualified specialists in domestic practice, who can practically carry out such a scan.